2010
DOI: 10.1515/libr.2010.011
|View full text |Cite
|
Sign up to set email alerts
|

Not what you know, nor who you know, but who you know already: Examining Online Information Sharing Behaviours in a Blogging Environment through the Lens of Social Exchange Theory

Abstract: This paper focuses on the extent to which online information sharing practice is socially motivated. A key interest is how knowledge of the existing social connections between actors may predict their information sharing behaviour when they move into an online environment, and the relative importance of these connections when set against other factors that may motivate online information sharing within a closed group. The examination of online information exchanges between members of a defined community of blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 25 publications
1
35
0
1
Order By: Relevance
“…Various studies have found that information sharing is affected by the strength of relationships, either within groups (Haythornthwaite, , pp. 327–328) or between individuals (Hall et al., , p. 14), with factors such as levels of friendship (Allen, , cited in Rioux, , p. 26) or the “socially contagious” nature of tagging (Ames & Naaman, , p. 978) influencing sharing.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Various studies have found that information sharing is affected by the strength of relationships, either within groups (Haythornthwaite, , pp. 327–328) or between individuals (Hall et al., , p. 14), with factors such as levels of friendship (Allen, , cited in Rioux, , p. 26) or the “socially contagious” nature of tagging (Ames & Naaman, , p. 978) influencing sharing.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The concept of information-sharing Information Technology for Development 301 behavior has been investigated in recent studies on online information use (See, e.g. Casaló, Flavián & Guinalíu, 2011;Hall, Widen, & Paterson, 2010;Lenhart, Purcell, Smith, & Zickuhr, 2010). However, the way in which factors such as group identification, trust, and social interaction play a role in information dissemination in real-world contexts has received far less research attention.…”
Section: Information-sharing Mechanismsmentioning
confidence: 99%
“…In several texts the concept of "knowledge sharing" seems to be used as a synonym to "information sharing" (e.g. Widén-Wulff and Davenport, 2005;Widén-Wulff, 2007;Tötterman and Widén-Wulff, 2007;Peel and Rowley, 2010;Hall et al, 2010). The next section of the article will concentrate on theoretical perspectives for information sharing.…”
Section: Conceptualisations Of Information Sharing -Between Broad Andmentioning
confidence: 99%
“…Haythornthwaite, 1996Haythornthwaite, , 2010Hall et al, 2010;Hersberger, 2003;Huotari and Chatman, 2001;Veinot, 2009). However, these approaches come with different flavours; how much the actual network dimension is emphasised varies.…”
Section: (Social) Network Analysismentioning
confidence: 99%
See 1 more Smart Citation